La haine à plusieurs visages dans les Chroniques du Plateau Mont Royal de Michel Tremblay - Kapołka, Karolina (Romanica Silesiana)
Karolina Kapołka deals with the conflict relationships between characters made by Michel Tremblay, a Quebec writer, in which hatred takes on a variety of forms: from direct to veilled and indirect. Keywords: hatred; dominance; family; mother; Tremblay